URGENSI MEMPELAJARI EKONOMI ISLAM ( Studi Motivasi Belajar Ekonomi Islam Pada Anggota Kelompok Studi Ekonomi Islam Fakultas Ekonomika dan Bisnis Universitas Diponegoro Semarang ) - Saleh, Ismail; Rahardja, Edy (Diponegoro Journal of Management, 2012)
The economic system of capitalism, socialism, or a combination of the two has proved a failure in creating the world's wealthy. The international community now has found another economic system as a solution that Islamic economic system. Perfection Islamic economic system both in terms of theory and practice has been increasingly recognized by the people of Moslem but also non-Islamic people. Therefore, it is crucial to study Islamic economics intensively because someone can know if it is important or not already know. The importance of studying Islamic economics should be well known by members KSEI FEB UNDIP so they must have a great motivation in studying Islamic economics. But from the initial observation shows that most members KSEI FEB UNDIP are less motivated to study intensively Islamic economics. The purpose of this study was to determine the effect of intrinsic factors and extrinsic motivation of Islamic economics KSEI member of FEB UNDIP. This study uses qualitative data collection conducted by the method of triangulation. The informants of this study is the HEI's senior who is a tutor of a weekly small discussion. The results of this study states that learning is intrinsically motivating factors consist of factors ideals, abilities, and conditions of each KSEI’s member both phisical and psychological (perceptions, interests, attitudes, intelligence). Psychological factor that comes from religious motives is a major influential factor in the intrinsic motivation to learn. While learning to extrinsic factors consist of social environmental factors (inside and outside KSEI), non-social environment (natural and instrumental) as well as the teachers in the learning effort. Mandate as an HEI’s senior and as a board of KSEI has been a major factor influencing extrinsic in motivation adding to the study of Islamic economic.